An ICT-Based Coumarin Fluorescent Probe for the Detection of Hydrazine and Its Application in Environmental Water Samples and Organisms - Liu, Xina; Zhu, Meiqing; Xu, Chenyang; Fan, Fugang; Chen, Panpan; Wang, Yi; Li, Dongyang (Frontiers in Bioengineering and Biotechnology, 2022)
As an inorganic small molecule pollutant, the toxicity and potential carcinogenicity of hydrazine (N2H4) are of increasing concern. In this work, A water-soluble fluorescent probe (OCYB) based on the intramolecular charge transfer (ICT) mechanism for the detection of hydrazine was designed and synthesized. Taking the advantage of 4-bromobutyryl as the recognition group, the high selectivity of OCYB to N2H4 was confirmed by steady-state fluorescence spectroscopy. The limit of detection (LOD) was calculated to be 78 nM in the DMSO-HEPES (pH 7.4) system. The detection mechanism was verified by NMR, HRMS and density functional theory (DFT) calculations. In addition, OCYB exhibits strong anti-interference ability and an “Off-On” fluorescence enhancement effect. Importantly, OCYB can be used to effectively monitor the fluorescence distribution of N2H4 in environmental water samples and organisms.